Mississippi’s Economy and its Impact on Higher Education Enrollment - Poole, Jacob N.; Kim, Donghyun (Journal of Applied Business and Economics, 2017)
This research examines the relationship between Mississippi’s statewide economy and the online enrollment statistics to major universities around the state. Online learning has been a growing trend in recent years and is becoming a cheaper alternative to some than going away to attend classes at a university while still getting a quality education. Therefore, it is important to consider the impact of Mississippi’s statewide economy to see how big of a role it plays into universities online enrollment rate versus their traditional enrollment. Several studies have considered the impact of online learning, but there is a lack of research regarding enrollment based on economic data.